Comparison of apically extruded debris of different nickel titanium instruments (Mustansiria Dental Journal, 2018)
AbstractBackground and objective: During root canal instrumentation irrigants, necroticpulp tissue, microorganism and dentin debris may be extruded beyond the apexinto the periradicular tissue. These extrusions may cause flare-up. The purpose ofthis study was to compare the amount of apically extruded debris with three rotaryNickel titanium instruments.Methods: Sixty single rooted, single canalled premolars were selected. The rootswere divided randomly into three groups; (n = 10) according to the type ofinstrumentation system used, group 1“ProTaper Next” system, group 2 “OneShape” system and group 3 “Mani Silk” system. The Debris extruded during theinstrumentation was collected and dried in preweighed vials and the amount ofextruded debris was assessed with an electronic balance.Result: results showed that the Mani silk system extruded significantly less debristhan the ProTaper Next and One shape systems (P < .05), and there is nosignificant difference in apically extruded debris between ProTaper Next groupand One Shape group but the One Shape produced more debris than ProTaperNext.Conclusion: the Mani silk file instrument was behaved well during instrumentationand extruded less debris than the other groups.